The Challenges of Down Syndrome Screening in Primary Healthcare for Pregnant Women in Iran in 2018 - Zeinaloo, Mona; Shariati, Mohammad; Younesian, Masoud; Kheiltash, Azita (Makara Journal of Health Research, 2024)
Background: This study aimed to evaluate the various aspects of the implementation phase, including an economic evaluation, of Iran’s Down syndrome (DS) screening program. Methods: Data were collected via phone interviews involving three random sample groups, with each group consisting of 1000 mothers who completed their pregnancies in 2018. To analyze the DS screening program from an economic aspect, we compared the costs related to the care of a DS individual in the country with that of finding and aborting a DS fetus based on the current screening program. In addition, to examine the financial expenses, we assessed the false positive rate (FPR) obtained from the tests and the status of pregnancy outcomes in terms of DS birth and the incidences of abortion complications in the interviewed samples. Results: A total of 94.5% of pregnant mothers participated in the DS screening program. The calculated FPRs in the screening tests were in the range of 15.3% (95% confidence interval (CI): 12.7%–18.1%) to 16.5% (95% CI: 13.7%–19.5%) for mothers registered in Iran’s Health Network and 12.5% (95% CI: 10.2%–15.2%) for all mothers. The results suggest the inefficiency of the current implementation of the DS screening program in Iran from an economic perspective and given the respective side effects, especially fetal loss. Conclusions: The DS screening program in Iran necessitates urgent review and modification.